Classroom environment and motivation to learn as correlates to academic achievement in Biology of College of Arts and Sciences freshmen students - Kuizon, Lily Beth C. (2010)
The study investigated the relationship of classroom environment and students' motivation to learn with their academic achievement in Biology. The two hundred fifty-six freshmen college students of the College of Arts and Sciences, Bukidnon State University participated in the study. The correlation research design was utilized in the study. Three research instruments were used: the College and University Classroom Environment Inventory (CUCEI) as adopted from Fraser (2002), the Motivation to Learn Questionnaire (Pintrich and Schunk, 1996) as adopted from Ortiz (1997), and the Biology Achievement Test. The data were treated using the mean, standard deviation, and the Product-Pearson (r) Moment Correlation at 0.05 confidence level. Generally, the students perceived that the classroom environment dimensions of: personalization, student cohesiveness, satisfaction, and innovation happen once in a while. Involvement, task orientation, and individualization happen most the time in the classroom. The motivation pattern of the freshmen college students to learn Biology was in the following order: maintenance, affiliation, competence, and achievement motivation. Generally, the academic achievement level in Biology of freshmen college students is failed. There is a statistically significant relationship of classroom environment with students' motivation to learn Biology. However, there is no statistically significant relationship of classroom environment with academic achievement. Students' motivation to learn is not statistically associated with their academic achievement in Biology.
Keywords: Mindanao studies